Strongly Bound Frenkel Excitons on TiO2 Nanoparticles: An Evolutionary and DFT Approach - Oscar Olvera-Neria; Raúl García-Cruz; Julio Gonzalez-Torres; Luz María García-Cruz; Jean Luis Castillo-Sánchez; Enrique Poulain (International Journal of Photoenergy)
An evolutionary algorithm was employed to locate the global minimum of TiO2n nanoparticles with n=2–20. More than 61,000 structures were calculated with a semiempirical method and reoptimized using density functional theory. The exciton binding energy of TiO2 nanoparticles was determined through the fundamental and optical band gap. Frenkel exciton energy scales as EB eV=8.07/n0.85, resulting in strongly bound excitons of 0.132–1.2 eV for about 1.4 nm nanoparticles. Although the exciton energy decreases with the system size, these tightly bound Frenkel excitons inhibit the separation of photogenerated charge carriers, making their application in photocatalysis and photovoltaic devices difficult, and imposing a minimum particle size. In contrast, the exciton binding energy of rutile is 4 meV, where the Wannier exciton energy scales as EB eV=13.61 μ/ε2. Moreover, the Wannier excitons in bulk TiO2 are delocalized according to the Bohr radii: 3.9 nm for anatase and 7.7 nm for rutile.